Enhancing Financial Decision-Making: Real Options Complementing the Net Present Value Technique in the Financial Services Sector - Ferina Marimuthu; Kyle Fitzgerald (Journal of Management and Entrepreneurship Research, 2024)
Objective: This study investigates the effectiveness of integrating real options with the Net Present Value (NPV) technique in the context of the financial services sector. The aim of the study was to assess how this approach enhances decision-making among financial practitioners. Research Design & Methods: Employing a quantitative research approach, data was collected through a questionnaire from 286 participants in the financial services sector who had prior experience in project evaluation and decision-making. Findings: The results concluded that the incorporation of real options into traditional NPV analysis significantly improves decision-making, offering decision-makers greater flexibility and efficiency. The results suggest that when faced with hypothetical projects where initial NPV turns negative with the adoption of real options, decision-makers are more likely to make rational choices that optimize the outcome. Implications and Recommendations: Based on the findings, the adoption of a combined NPV and real options strategy for practitioners in the financial services sector is recommended in order to make more informed and flexible investment decisions, which would ultimately benefit their organizations and stakeholders. Contribution & Value Added: Future research should explore the qualitative aspects of decision-making and expand the analysis to different nations and industries.